Penyusunan Laporan Keuangan UMKM Berdasarkan SAK EMKM Pada Usaha Kecil Menengah Prata Frozen Karlifood Periode Januari-Desember 2024 - Mutia Putri Marisa; Emilia Cahya Febriana Sari; Andrea Nova Maraza Zuliansyah; Hadli Lidya Rikayana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to prepare financial statements for the MSME Prata Frozen Karlifood based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) and to evaluate the conformity of the enterprise’s financial recording practices with these standards. The research employed a descriptive quantitative approach using primary numerical data such as transaction reports, production costs, and daily financial records. In addition, interviews, observations, and documentation were used to provide supporting qualitative insights into the business’s recording practices. The results show that the MSME’s initial financial records were simple and not aligned with standardized reporting structures; however, after data processing and restructuring according to SAK EMKM, the statement of financial position, income statement, and notes to the financial statements were successfully presented in a more accurate and structured format.